Association of Normal vs Abnormal Meary Angle With Hindfoot Malalignment and First Metatarsal Rotation: A Short Report. (May 2022) - Steadman, Jesse; Bakshi, Neil; Philippi, Matthew; Arena, Christopher; Leake, Richard; Barg, Alexej; Saltzman, Charles L.
Background: Recent work has reported a significant association between first metatarsal (M1) rotation and hindfoot alignment, with the finding of a moderate association between the calcaneal moment arm (CMA) and 2 M1 pronation angular measures: Saltzman ( r = 0.641, P < .01) and Kim ( r = 0.615, P < .01). The aim of the current post hoc investigation was to determine if this association is related with Meary angle. Methods: We reanalyzed previously published data set separating patients into 2 groups: (1) those with normal Meary angle (n = 128) and (2) those with abnormal Meary angle (n = 147). Hindfoot alignment and M1 rotation were measured on weightbearing computed tomography. Statistical analyses were performed to evaluate for association between these variables among the groups. Results: The correlation between CMA and M1 rotation of the entire cohort was r = 0.577 (Saltzman ankle) and r = 0.540 (Kim angle). For the subset with a normal Meary angle, this association was negligible (Saltzman and Kim angles, r = 0.194 and 0.240, respectively). Conversely, for the abnormal Meary angle subset, the association was substantial (Saltzman and Kim angles, r = 0.733 and 0.675, respectively). Conclusion: Patients presenting with an abnormal Meary angle and hindfoot deformity have a high likelihood of manifesting a proportionate degree of M1 rotation. Level of Evidence: Level III, Retrospective Cohort Study.